Impact of government science and technology policies with a focus on biotechnology research on commercial agricultural innovation in China. Issue 3 (4th September 2017) - Jin, Yanhong; Hu, Yahong; Pray, Carl; Hu, Ruifa
Abstract : Purpose: The Chinese Government has used a number of policies to encourage commercial agribusiness firms to do more innovation. These include public sector agricultural research and development (R&D), public sector biotechnology research and innovation, subsidies for commercial research, encouraging foreign firms to invest in China as minority shareholders in joint ventures, and allowing commercial companies to raise money on the stock market. The purpose of this paper is to assess whether these policies were effective in stimulating innovations by commercial firms in China. Design/methodology/approach: This study estimates the impact of public biotech research and other policies by employing an econometric model of patenting by commercial firms. It uses a unique data set collected from commercial agribusiness firms for the years 2001, 2004, 2005, and 2006. Addition data were collected from public research institutes and universities and patent data from the Derwent Innovations Index database. It employs four count data models for the empirical analysis. Findings: This study finds a positive impact of public biotechnology (measured by the number of biotech patents of government research institutes and public universities) on commercial innovation measured by the number of patents granted to the commercial firms. As expected the firm's research expenditure and having their own R&D center (as opposed to contracting R&D or no R&D investment at all) have a positive and statistically significant effect on the number of patents granted. The impacts of public R&D investment spending have no statistically significant effect on commercial innovation. Multi-national firms and publicly traded firms have fewer patents than their counterparts suggesting that policies to encourage multi-nationals and financing through stock markets had no impact on innovation. Originality/value: This study is one of the first studies to untangle the relationship between government policies and innovation by commercial agricultural research output and public R&D investment and biotechnology. The main findings suggest that simply increasing research money to public research does not increase commercial innovations, but moving resources to the development patentable biotech does improve commercial research productivity. The results also suggest that policies to increase commercial research will also increase innovation. These could include strengthening the legal framework and institutional resources for public institutes to the protection and enforcement of intellectual properties.